Thymol Nanopolymer Synthesis and Its Effects on Morphine Withdrawal Syndrome in Comparison With Clonidine in Rats - Moayeri, Ardeshir; Mehdizadeh, Reza; Karimi, Elahe; Aidy, Ali; Ghaneialvar, Hori; Abbasi, Naser (Frontiers in Behavioral Neuroscience, 2022)
The drug delivery system is valuable in the treatment of the disease. A nanopolymer as a thymol and Thymbra spicata release system was synthesized and its effects on morphine withdrawal syndrome in comparison with clonidine in rats were studied. The nanopolymer was characterized by different methods including IR, HNMR, CNMR, GPC, DLS, and AFM. Thymol in Thymbra spicata extract was assessed. The loading and release rate of thymol and Thymbra spicata extract on the nanopolymer were evaluated by HPLC. The median lethal dose (LD50) of the Thymbra spicata extract, thymol, extract nanopolymer and thymol nanopolymer were studied. frequency of jumping, rearing, and teeth chattering in naloxone-induced morphine withdrawal syndrome was studied. Synthesized nanopolymer was desirable as a carrier for the drug. The loaded amount of extract and thymol on nanopolymer estimated 55 ± 3.2 % and 48± 2.6% and the drug released was 71% and 68%, respectively. LD50 of the Thymbra spicata extract, thymol, extract nanopolymer and thymol nanopolymer were 975, 580, 1250, and 650 mg/kg, respectively. This study showed that thymol nanopolymer was more effective than clonidine to reduce the frequency of morphine withdrawal symptoms. Our results suggest that Thymbra spicata extract, thymol, extract nanopolymer and thymol nanopolymer are mighty of reducing the narcotic withdrawal signs. The mechanism of action and therapeutic potential is maybe similar to clonidine.